PENERAPAN METODE IQRA PADA PENDIDIKAN AL-QUR’AN DI SEKOLAH DASAR ALAM MUHAMMADIYAH BANJARBARU - Muhammad Rahman; Imaniah Elfa Rachmah (DARRIS: Jurnal Pendidikan Madrasah Ibtidaiyah, 2018)
This study discusses the application of the method of Iqra on the education of the Holy Qur'an in Nature primary school Muhammadiyah Banjarbaru. Formulation of the problem in this research is how the application of the method of Iqra Qur'an education in primary school Muhammadiyah Banjarbaru and Natural factors that affected it. Based on the formulation of the problem, then the purpose of this research is to know the application of methods of Iqra on the education of the Holy Qur'an in Nature primary school Muhammadiyah Banjarbaru and factors which affected it. The subject in this study was the educator of the Qur'an and the students of class V Natural primary school Muhammadiyah Banjarbaru. While the object examined is an application of a method of Iqra on the education of the Holy Qur'an in primary school Muhammadiyah Banjarbaru. Data collection techniques in the study use techniques of observation, interview and documentation. While the techniques of data processing are done by editing, data classification, and interpretation of data, further analyzed in qualitative descriptive and inductive conclusions are drawn. Based on the results of the research it is known that the application of the method of Iqra on Qur'an education which has been implemented by the natural primary school Muhammadiyah Banjarbaru is already well underway. This can be seen through the results of the learning learners using the method of Iqra, which learners can read Quran properly. Though indeed there is still a part of learners is still not right in reading the Qur'an. As for the factors that influence the application of the method of Iqra on Qur'an education primary school Muhammadiyah Natural Place includes the following: (1) factors of learners. (2) factors for educators. (3) environmental factors. (4) the Association Factor. (5) the allocation of the Factors of the time. The whole of these factors is influencing and supporting in the application of the method of education at the Iqra Qur'an. Keywords: Education, learning methods of the Qur'an, Iqra.